¿Es la terapia danza-movimiento un método eficaz para la depresión en jóvenes? - Parodi Castro, María Alejandra (2024)
Depression is the biggest cause of disability worldwide. The aim of this study was to identify the efficiency of Dance Movement Therapy (DMT) in young adults with depression throughout evidence-based articles. Depression is defined by a decrease in mood, dysphoria, deteriorated motivation, and other symptoms such as motor and cognitive disturbance. On the other hand, DMT is the use of dance as a therapeutic method to integrate the emotional, cognitive, physical, and social aspects of the person. We performed an academic search using Scopus as our main database, selecting a total of 10 quantitative experimental articles that measured the effect of DMT on depressed patients (n = 10). The methodology used in most of the studies was quantitative experimental where Beck's Depression Inventory was applied on most of them, pre and post DMT intervention to measure the efficiency of this therapy. This consisted of 10 to 20 weeks of DMT sessions with the patients where it was concluded that DMT had a positive effect on depression. It would benefit future investigations to analyze this with a reduced age range and Latin American populations.